2021
DOI: 10.1001/jamaneurol.2021.0405
|View full text |Cite
|
Sign up to set email alerts
|

Ponesimod Compared With Teriflunomide in Patients With Relapsing Multiple Sclerosis in the Active-Comparator Phase 3 OPTIMUM Study

Abstract: IMPORTANCE To our knowledge, the Oral Ponesimod Versus Teriflunomide In Relapsing Multiple Sclerosis (OPTIMUM) trial is the first phase 3 study comparing 2 oral disease-modifying therapies for relapsing multiple sclerosis (RMS).OBJECTIVE To compare the efficacy of ponesimod, a selective sphingosine-1-phosphate receptor 1 (S1P 1 ) modulator with teriflunomide, a pyrimidine synthesis inhibitor, approved for the treatment of patients with RMS. DESIGN, SETTING, AND PARTICIPANTSThis multicenter, double-blind, activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
168
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(171 citation statements)
references
References 44 publications
(75 reference statements)
0
168
0
3
Order By: Relevance
“…As all approved S1PR modulators engage S1P 1 , including singly through ponesimod that exhibited unbiased functional antagonism in human astrocytes, it appears that major benefits accrue through functional antagonism of this receptor subtype. The novel reduction in MS fatigue accessed by ponesimod 16 underscores the benefits, particularly through CNS mechanisms that involve complex cell autonomous and non‐cell autonomous interactions, which may reveal novel therapeutic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As all approved S1PR modulators engage S1P 1 , including singly through ponesimod that exhibited unbiased functional antagonism in human astrocytes, it appears that major benefits accrue through functional antagonism of this receptor subtype. The novel reduction in MS fatigue accessed by ponesimod 16 underscores the benefits, particularly through CNS mechanisms that involve complex cell autonomous and non‐cell autonomous interactions, which may reveal novel therapeutic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Since ponesimod is only supposed to engage S1P 1 , it provided an opportunity to examine its mechanistic effects as a mono‐specific S1P 1 receptor modulator beyond the previously reported peripheral immunological effects 18 . Other effects included those relevant to ponesimod clinical trial data (OPTIMUM Phase 3 study) 16 that achieved a novel secondary endpoint of reduced MS fatigue. Independent examination of ponesimod was therefore pursued for receptor selectivity, human astrocyte signaling, single‐cell gene expression, and an animal model of cuprizone‐induced demyelination that might elucidate the mechanisms underlying ponesimod efficacy signals related to MS fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…In EAE models, ponesimod was found to be effective in both preventive and therapeutic settings in which the overall severity of MS was reduced; this effect was also observed through improved histological outcomes (Pouzol et al, 2019). Recently, a Phase III, active-comparator, randomized trial demonstrated that ponesimod was superior to teriflunomide on annualized relapse rate reduction (the primary study outcome), fatigue symptoms, and MRI activity (Kappos et al, 2021). However, a search of the literature did not identify any published studies on the effects of ponesimod on the integrity of the BBB, or the CNS penetration of the drug in patients with MS.…”
Section: Ponesimodmentioning
confidence: 99%
“…Compared with the previous two members of the same class, Ozanimod facilitates a quicker lymphocyte reconstitution after discontinuation. Ponesimod is a selective S1PR-1 modulator that has been evaluated by authorities and recently received approval for active RRMS treatment by the EMA [121][122][123].…”
Section: Chronic Ms Dmts With Central Effect Beyond the Bbbmentioning
confidence: 99%